Belief-based Tobacco Smoking Scale: Evaluating the PsychometricProperties of the Theory of Planned Behavior's Constructs - Majid Barati; Hamid Allahverdipour; Alireza Hidarnia; Shamsodin Niknami; Saeed Bashirian (Tabriz University of Medical Sciences, 2015)
Background: At present, there are no comprehensive validated instruments for measuring adolescents' beliefs regarding tobacco smoking in the Iranian society. This study aimed to evaluate the validity, reliability and feasibility of the belief-based tobacco smoking scale using the Theory of Planned Behavior's (TPB) constructs as a theoretical framework.Methods: This cross-sectional validation study was carried out on 410 male adolescents of Hamadan, west of Iran, recruited through multi-stage random sampling method. Reliability was assessed by internal consistency and Intraclass Correlation Coefficient (ICC). In addition, Confirmatory Factor Analyses (CFA) and Exploratory Factor Analyses (EFA) were performed to test construct valid-ity. Content validity was examined using Content Validity Index (CVI) and Con-tent Validity Ratio (CVR).Results: Results obtained from factor analysis showed that the data was fit to the model (X2=391.43, P<0.001) and TPB consisted of 22 items measuring sev-en components which explaining 69.7% of the common variance. The mean scores for the CVI and CVR were 0.89 and 0.80; respectively. Additional anal-yses indicated acceptable results for internal consistency reliability values ranging from 0.55 to 0.92.Conclusion: The belief-based tobacco smoking questionnaire is a reliable and valid instrument and now is acceptable and suitable and can be used in future studies.